Nature's Role in Democratic Societies: A Conversation Between Whitman and Melville - Mendonca, Alyssa (Spectrum, 2023)
Writing about seventy years after the 1776 Declaration of Independence and the 1789 American Constitution, both Herman Melville and Walt Whitman grapple with the viability of American democracy by presenting either a suppression or celebration of alternative visions. In Melville’s Moby Dick, the multivalent relationship between man and nature is realized aboard the Pequod as its diverse crew takes different stances on the merits of Ahab’s vengeful hunt. The novel details the suffocation of a democratic vision under the guise of a ‘unified’ mission that is ultimately exclusionary and despotic. Walt Whitman’s “Song of Myself” handles the same themes of man, nature, and the democratic principles of inclusion, diversity, and equality differently, creating an actual unified vision that maintains its integrity by absorbing and accommodating difference. Considering both authors’ use of the body as a symbol and a syntactic relationship to alternative visions, Whitman’s poem offers a critique of Melville’s handling of these elements, suggesting that checking nature but not the ego will yield tragedy and tyranny.